THE IMPACT OF ARTIFICIAL INTELLIGENCE ON LANGUAGE LEARNING - Nilufar Ochilova (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Artificial intelligence (AI) is bringing significant changes to the field of education, especially in the methods of language learning. Through adaptive systems, personalized feedback, and natural language processing (NLP) tools, AI offers new opportunities for students and teachers to improve the learning process.